Wear and affect: cosmetic obsolescence of plastics in digital products - Alan Manley; Debra Lilley; Karl Hurn (2015)
The relationship we have with materials is built up over time and includes a complex array of variables that contribute to a material having preconceived functional and aesthetic qualities that are specific to certain products and within certain materials (Demirbilek & Sener, 2003, Dunne, 2005; Chapman, 2015). The relationship we have with plastic is a short one and has not yet been fully understood in terms of our material culture. The use of plastics for the manufacture of digital goods is interesting, as the brevity of our relationship with plastics as a material is mirrored by our short lived contact with rapidly obsolescing digital products. As a result the opportunities to engage with the material and to understand how it ages over time are limited. If we are to encourage the extension of digital product lifetimes, it is imperative that we understand the way plastics age within this context. The disposal of digital products (of which significant proportions are manufactured using a variety of plastics) contributes to a substantial problem of e-waste. The most recent estimation is that around £200m of digital products per year are sent to landfill (WRAP, 2015). The physical condition of these devices is an important factor in product replacement, which leads to significant product turnover (van Nes, 2004; Cooper, 2010). To understand the reasons for disposal of these digital devices, cosmetic obsolescence is the area that this paper is concerned with and through empirical studies, the paper establishes how smartphones [in this instance] wear over time and what the attitudinal reactions to those instances of wear are. By conducting these studies, a taxonomy of wear is established that occurs within plastics used in digital products and begins to understand the attitudinal reactions which give an indication of the affect that these types of wear have on the perceptions of plastics in terms of newness and tolerance of wear.